An empirical analysis of cleaning frequency impacts on the process performance of a lab scale gas-sparged AnMBR treating swine wastewater - Williams, Jordan (Kansas State University, 2024)
For 9,000 years, pigs have been intertwined with human societies, as our population rose from 10-20 million to 8 billion today. Global swine rearing has expanded alongside human development, straining the Earth's waste management capacity. Climate change-induced disaster and the eminent crossing of planetary boundaries in phosphorus and nitrogen utilization emphasize the urgent need for efficient waste management. Swine, primarily and increasingly raised in concentrated animal feedlot systems (CAFOs), generate excessive manure, leading to as much as 170 million tons CO₂e emissions and significant financial losses in the form of wasted nitrogen and phosphorus, loss of ecosystem services, environmental remediation, and uncaptured energy potential. Improved swine manure management is crucial for sustainable development. The Anaerobic Membrane Bioreactor (AnMBR) holds potential as a treatment and resource recovery solution, aiming for net-zero or energy-negative operation. However, membrane fouling challenges treatment efficiency and cost-effectiveness. To date, there have been only a few lab and bench scale studies on swine wastewater treatment with AnMBRs, most of which use a synthetic or controlled swine waste influent (by dilution and mixing with synthetic solutions) and focus on acclimation of the microbial community and COD conversion to methane. While these studies have implemented various fouling management technologies, further research into energy optimization of AnMBRs treating high-strength waste streams like swine manure is warranted given the technology's novelty. This study seeks to explore optimization options for a completely submerged AnMBR configuration using common fouling management techniques and real, highly variable swine wastewater influent. The completely submerged, continuously gas sparged 114.7 L AnMBR was operated in two discrete phases, both targeting distinct objectives. Phase I aimed to minimize chemical cleaning footprint for fouling control while preserving membrane performance and permeate flux. The volumes of citric acid and bleach used for CIP maintenance were limited to 250 mL per 10-minute cleaning cycle compared to the manufacturer protocol of 15 L for 5 hours, and the cleaning frequency was varied between 0.37 and 2.5 times per week over 244 days (manufacturer recommendation of 2.0 times per week). 60-80% COD removal was observed during this period, which is low for such systems. The highest average permeability recovery (15.2%) and recovery efficiency (23.8%/%) were observed during the Case 2. However, no correlation was established between cleaning frequency and permeability recovery. The average overall flux was maintained at an acceptable 10.2 LMH, supporting that cleaning schedule may have little impact on gas sparged AnMBR efficiency and can likely be significantly reduced compared to conservative manufacturer recommendations. Phase II, spanning 114 days, used higher strength waste and sustained a more consistent operation schedule under a constant but reduced cleaning schedule, and demonstrated consistent average COD and BOD removal (87.9% and 90.7% respectively) comparable to high-performance anaerobic and facultative lagoon systems and low to mid performance AnMBRs, with an average HRT of 7.6 days, significantly shorter than traditional AD systems (20-75 days). Effluent turbidity stayed within range for indirect reuse (average: 0.44 NTU), indicating superior solids removal. Between days 52 and 103, an estimated 45.6% of the COD input was converted to methane in the headspace biogas, which is in line with expectations for these systems (30-75%). The average methane concentration in the biogas was 72.6%, with a peak of 81.9%, showing promise for upgradation to pipeline injection standard, and further supporting that gas sparging for fouling mitigation has the added benefit of enriching the biogas methane content by leveraging the greater solubility of CO₂ compared to CH₄. Due to the consistent operation, gas greater permeability recovery (average +2.44% pts) than chemically enhanced backpulse (CEB), which further supports that gas sparging with passive batch recovery (PBR) may be a preferred method of fouling management in swine AnMBRs to CEB. An initial modeling framework to model fouling behavior in continuously gas sparged, submerged AnMBRs was developed that successfully described 67% of the observed data and demonstrated an R² 0.8892 when the real data was plotted against the predictions. This indicates there is promise for In summary, the findings of this study agree with past observations from AnMBR operation and support that the high performance and energy recovery potential of such systems can be extended to swine wastewater, a prevalent waste stream and polluter. The resilience of superior COD and BOD₅ removal to variable organic loading rates increases confidence in the capability of AnMBRs to manage high strength wastewaters. It also supports that gas sparging as a fouling management option has added benefit by significantly reducing chemical cleaning footprint and enriching methane content of biogas.
Keywords: Membrane fouling; Swine wastewater; Resource recovery; Energy optimization; Biogas; AnMBR anaerobic digestion